A profissionalização de 2. grau em São Luís do Maranhão - Lima, Maria do Socorro Quariguasi (1984)
This study intends to characterize and delineate the content expressed by the text of the Law 5.692/71, emphasizing the professional teaching question. It is organized in six chapters. The first chapter presents the educationa1 process as it is occurring within our capitalis tic society . In the second, the line of his teorical context analysis is folllowed, having the goal of touching the ideology of the Law 5.692/71 text. The third describes the problem and the methodology of a case study realized in São Luís do Maranhão, it's results beeing presented in the fourth chapter and analysed in the fifth chapter. The last chapter contains the author's conclusions. This work makes evident that the legal text in question undertakes very well the ideological functions that are handled by the state, viewing to attend the society's reality by means of social reproduction anel perpetuation mechanisms, in spite of beeing confirmed the alienation of students that conclude professional courses, alienation due to the fact of not beeing them absorved by the market. It becomes clear that the intellectual and scholastic performance differences are the barriers disciosed in class society, enhabling the school apparatus to be free for the maintenance of its functions. The study results show that the school warrants a manual labor supply, through the disguised mechanism of 'not preparing to a profession', as the great majority of students that went out professional courses are unemployed. The study conclusions point to the necessity of mobilizing the professional teaching, in order more actively and powerfully in relation to the context necessities. In the way it is presently carried out, this type of teaching do not distinguish itself too much from the confection of machines or toils, because it serves more the production system than the man - as we see by the fact of not beeing programed any employment warranty. It leads consequently to man's 'dishumanization'.